Evaluation of an Intensive Interdisciplinary Pain Treatment Based on Acceptance and Commitment Therapy for Adolescents With Chronic Pain and Their Parents: A Nonrandomized Clinical Trial. (17th May 2018) - Kemani, Mike K; Kanstrup, Marie; Jordan, Abbie; Caes, Line; Gauntlett-Gilbert, Jeremy
Abstract: Objective: Parental factors are central in the development and maintenance of chronic pain in youths. Only a handful of studies have investigated the impact of psychological treatments for pediatric chronic pain on parental factors, and the relationships between changes in parental and adolescent factors. In the current study, we evaluated the effects of an intensive interdisciplinary pain treatment (IIPT) program based on Acceptance and Commitment Therapy (ACT) for adolescents with chronic pain, on adolescent and parental variables, and the relationship between parental psychological flexibility and adolescent pain acceptance. Methods: Adolescents ( N = 164) with chronic pain were included, with a mean age of 15.5 years, and completed the 3-week treatment with an accompanying parent ( N = 164). Linear mixed-effects models were used to analyze change over time (from pretreatment to 3-month follow-up) on parent (depression, health-related quality of life and parent psychological flexibility) and adolescent (physical, social and emotional functioning, and adolescent pain acceptance) variables. Additionally, linear mixed-effects models were used to analyze the relationship between parent psychological flexibility and adolescent pain acceptance. Results: Results illustrated significant improvements over time in depressive symptoms and levels of psychological flexibility in parents. Excluding social development, adolescents improved significantly in all assessed aspects of functioning and pain acceptance. Additionally, changes in parent psychological flexibility were significantly associated with changes in adolescent pain acceptance. Conclusions: Results indicated that treatment had positive effects for parents and adolescents, and a significant positive relationship between changes in parent psychological flexibility and adolescent pain acceptance was found.